College Enquiry Chatbot - S, Janapreethi; S, Janapriya; M, Sarulatha; Hemalakshmi, G.R. (2023 2nd International Conference on Vision Towards Emerging Trends in Communication and Networking Technologies (ViTECoN), 2023)
Today's widespread use of smartphones is proof that technology is always evolving. Nowadays, artificial intelligence is crucial to numerous industries, including manufacturing, human resources, and customer service. There are numerous chatbots that help people discover solutions to their questions. As a result, we are developing an AI-powered chatbot that can address all questions about colleges. It serves as an intelligence tool with an emphasis on higher education. This artificially intelligent machine will respond to queries from users regarding matters related to higher education. The information is kept in the chatbot's database so that it can be used to spot trends and decide how to respond to questions. The chatbot for college inquiries was developed using an NLP system that evaluates questions and comprehends messages. People react to each other differently based on emotions and attitude. Because chatbots must go by rules just like humans do, they will communicate with customers in a courteous and correct manner. Students can ask the chatbot any questions at any time of the day or night, and they will receive a prompt and accurate response. A chatbot can respond to thousands of users simultaneously. Chatbot can work 24 ×7 without getting tired. It has minimal errors, which increases productivity.